2016
DOI: 10.1080/14786419.2015.1135143
|View full text |Cite
|
Sign up to set email alerts
|

Carbazole-pyranocoumarin conjugate and two carbazole alkaloids from the stems of Clausena excavata

Abstract: A carbazole-pyranocoumarin conjugate, carbazomarin B (1), and two carbazole alkaloids, 6-methoxymukonidine (2) and 2-hydroxy-3-methoxycarbazole (3), together with 27 known compounds (4-30), were isolated from the stems of Clausena excavata. Their structures have been elucidated by spectroscopic analyses. Compound 2 showed moderate cytotoxicity to HuCCA-1, MOLT-3 and HepG2 cancer cell lines with IC50 values of 15.09-28.50 μg/mL, but none to A549 cell line. Heptaphylline (6) and nordentatin (23) were found to sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…This type of binary compounds previously has been reported from C. excavata as carbazomarin-A 10 and carbazomarin-B. 11 The spectral data of 1 in pyranocoumarin unit are the same as the previously reported compounds. However, the carbazole unit is different from 1 .…”
supporting
confidence: 77%
“…This type of binary compounds previously has been reported from C. excavata as carbazomarin-A 10 and carbazomarin-B. 11 The spectral data of 1 in pyranocoumarin unit are the same as the previously reported compounds. However, the carbazole unit is different from 1 .…”
supporting
confidence: 77%
“…Its molecular formula was determined as C 32 H 28 N 2 O 3 base on its 13 C NMR and HRESIMS data ( m / z 487.2016 [M − H] − , calcd for C 32 H 27 N 2 O 3 , 487.2022). The 1 H and 13 C NMR data ( Table 2 and Table 3 ) analysis revealed that the structure of 17 is a dimeric carbazole formed by murrayamine A [ 16 ] and murrayafoline A [ 22 , 23 ] units. Additionally, the HMBC correlations from the 3″-CH 2 protons to C-5/C-6/C-7/C-2″/C-3″/C-4″, and H-5/H-2″/H-4″ to 3″-CH 2 revealed a C-6–C-3″-methyl linkage between the two carbazole moieties ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Due to the sensitivity of brine shrimp to a variety of chemical substances, many researchers had considered this assay for searching potent noncytotoxic natural compounds having biological and pharmacological properties [23][24][25]. Although previous studies showed antimicrobial activity of the bark, leaf, and stem of this plant [26,27], there is no recorded data for anti-Enterococcus faecalis.…”
Section: Introductionmentioning
confidence: 99%